A deep population reference panel of tandem repeat variation - Helyaneh Ziaei Jam; Yang Li; Ross DeVito; Nima Mousavi; Nichole Ma; Ibra Lujumba; Yagoub Adam; Mikhail Maksimov; Bonnie Huang; Egor Dolzhenko; Yunjiang Qiu; Fredrick Elishama Kakembo; et al. (Nature Communications, 2023)
Abstract Tandem repeats (TRs) represent one of the largest sources of genetic variation in humans and are implicated in a range of phenotypes. Here we present a deep characterization of TR variation based on high coverage whole genome sequencing from 3550 diverse individuals from the 1000 Genomes Project and H3Africa cohorts. We develop a method, EnsembleTR, to integrate genotypes from four separate methods resulting in high-quality genotypes at more than 1.7 million TR loci. Our catalog reveals novel sequence features influencing TR heterozygosity, identifies population-specific trinucleotide expansions, and finds hundreds of novel eQTL signals. Finally, we generate a phased haplotype panel which can be used to impute most TRs from nearby single nucleotide polymorphisms (SNPs) with high accuracy. Overall, the TR genotypes and reference haplotype panel generated here will serve as valuable resources for future genome-wide and population-wide studies of TRs and their role in human phenotypes.